A Systematic Review of Methods and Study Quality of Economic Evaluations for the Treatment of Schizophrenia - Wang, Luying; Shi, Fenghao; Guan, Xin; Xu, He; Liu, Jing; Li, Hongchao (Frontiers in Public Health, 2021)
Background: Schizophrenia is a severe and complex disease with substantial economic and social burdens. Despite multiple treatment choices, adverse events, and impaired social functions are still challenges in clinical therapy. Pharmacoeconomic evaluations could provide evidence to help decision makers improve the utilization of scarce resources. However, there remains some challenges especially in modeling due to uncertainties in progression of schizophrenia. There are limited summaries about the overall methodologies of schizophrenia economic evaluations. Objective: The aim of this study is to review the existing economic evaluations of antipsychotics for the treatment of schizophrenia and summarize the evidence and methods applied. Methods: An electronic literature search was performed in PubMed, Web of Science, EBSCO host, The Cochrane Library and ScienceDirect from January 2014 to December 2020. Search terms included “schizophrenia,” “schizophrenic,” “pharmacoeconomic,” “economic evaluation,” “cost-effectiveness,” and “cost-utility.” The Literature was screened and extracted by two researchers independently and assessed with the Quality of Health Economic Studies (QHES) List and Consolidated Health Economic Evaluation Reporting Standards (CHEERS) Statement. Results: A total of 25 studies were included in the review. The regions included Europe, North America, Asia and Africa. Most of the studies chose second-generation antipsychotics as comparators and integrated treatment sequences. Time horizons varied from 1 year to lifetime. The healthcare sector was the most common perspective, accordingly, most of the evaluations considered only direct medical costs. The Markov model and decision tree model were the most common choices. Adverse events, compliance and persistence were considered important parameters. Quality-adjusted life-years were the major outcomes applied to the economic evaluations. All utilities for health states and adverse events were collected from published literature. All of the studies applied uncertainty analysis to explore the robustness of the results. The quality of the studies was generally satisfactory. However, improvements were needed in the choice of time horizons, the measurements of outcomes and the descriptions of assumptions. Conclusions: This study highlights the methodology of economic evaluation of schizophrenia. Recommendations for modeling method and future study are provided.